2010
DOI: 10.1038/modpathol.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expressed sequence hybridization studies of t(11;18)(q21;q21)-positive and -negative gastric MALT lymphomas reveal both unique and overlapping gene programs

Abstract: Among the genetic abnormalities reported to occur in MALT lymphomas, the translocation t(11;18)(q21;q21) is of particular interest because it is exclusively documented in MALT lymphomas, mainly with gastrointestinal location. It results in the creation of a fusion protein API2-MALT1 that activates the transcription factor NF-jB through enhanced IKKc polyubiquitination. Here, we apply the recently developed molecular technique termed comparative expressed sequence hybridization to identify differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The API2 gene inhibits apoptosis whereas the MALT1 gene is believed to have its effect via activation of nuclear factor-κB [4]. This translocation mutation is believed to promote lymphoma cell survival and proliferation [5]. Unfortunately, about 30% of gastric marginal zone B cell lymphomas of MALT type have this mutation which carries a poor prognosis for treatment alone with antibiotics (22.2% remission rate).…”
Section: Commentsmentioning
confidence: 98%
“…The API2 gene inhibits apoptosis whereas the MALT1 gene is believed to have its effect via activation of nuclear factor-κB [4]. This translocation mutation is believed to promote lymphoma cell survival and proliferation [5]. Unfortunately, about 30% of gastric marginal zone B cell lymphomas of MALT type have this mutation which carries a poor prognosis for treatment alone with antibiotics (22.2% remission rate).…”
Section: Commentsmentioning
confidence: 98%
“…Interestingly, HP-negative MALT lymphomas have shown a high frequency of positive t(11;18) (q21;q21) [ 72 ]. This translocation event leads to the formation of a fusion protein called API2-MALT1, which in turn activates the transcription factor NF-kappa through enhanced IKK gamma polyubiquitination [ 73 ]. The above findings suggest that t(11;18)(q21;q21) may be a major contributor to the development of gastric MALT lymphoma and is associated with a poor prognosis [ 73 ].…”
Section: Gastric Mucosa-associated Lymphoid Tissue Lymphomamentioning
confidence: 99%
“…The recently described method comparatively expressed sequence hybridization, a sort of comparative genetic hybridization for RNA expression profiles, was used by Sagaert et al [17] to compare t(11,18)-positive and t (11,18)-negative gastric MALT lymphomas, normal gastric mucosa, and microdissected splenic marginal zone cells. They found that the expression profiles differed between the two types of MALT lymphoma and were even different according to the site of the chromosomal breakpoint, but they could also define a MALT-lymphoma signature that differentiates from normal gastric mucosa and a signature that overlaps with splenic marginal zone B cell.…”
Section: B-cell Lymphomasmentioning
confidence: 99%